2020
DOI: 10.1021/acs.langmuir.0c01315
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Wearable and Flexible Humidity Sensor Based on Graphene Oxide/Non-Woven Fabric for Respiration Monitoring

Abstract: The popularity of humidity sensing for respiratory analysis of patients is gradually increasing because of its portability and cost-effectiveness. However, current flexible humidity sensors are mainly made of polymer films, whose poor hygroscopicity and breathability reduce their sensitivity and comfort. In this study, a highly sensitive humidity sensor was developed using non-woven fabric (NWF) coated with graphene oxide (GO). Bovine serum albumin was used to improve the adsorption of GO onto the NWF, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 36 publications
1
81
0
Order By: Relevance
“…(c) Silver nanoparticles inkjet printed on paper to fabricate a flexible temperature sensor, reprinted with permission from [14]. (d) Graphene Oxide deposited on fabric for humidity sensing, reprinted with permission from [15]. [12].…”
Section: Figurementioning
confidence: 99%
“…(c) Silver nanoparticles inkjet printed on paper to fabricate a flexible temperature sensor, reprinted with permission from [14]. (d) Graphene Oxide deposited on fabric for humidity sensing, reprinted with permission from [15]. [12].…”
Section: Figurementioning
confidence: 99%
“…These flexible sensors were bent 8000 times and remained operable, demonstrating their excellent flexibility and reliability for industrial applications. Another humidity sensor based on non-woven fabric and graphene oxide was developed in 2020 for respiration monitoring to support healthcare delivery in response to the COVID19 pandemic [10]. The researchers claim that the non-woven material ranks above polymer materials when fabricating flexible sensors due to the poor hygroscopicity and breathability of polymers which limits their comfortability and sensitivity.…”
Section: Humidity Sensorsmentioning
confidence: 99%
“…Among these 2D materials, graphene was given great attention due to its excellent properties of high conductivity, the large specific surface area of 2600 m 2 g −1 , being optically transparent and having high chemical stability. Therefore, graphene and its derivative composites were widely investigated for the application of sensing change in humidity like SnO 2 /reduced graphene oxide (RGO) [33], methyl red/graphene flakes [34], black phosphorous (BP)/graphene [35], lignosulfonate/RGO [36], BP/graphene oxide (GO) [37], non-woven fabric/GO [38], orange die/graphene [39], graphene/polyvinyl alcohol (PVA)/SiO 2 [40], chitosan/graphene quantum dots [41], etc. Studies have shown that the structure of graphene has a huge impact on the properties of the humidity sensor; therefore, graphene has been used in different forms with ZnO to enhance the humidity sensing behavior of ZnO.…”
Section: Introductionmentioning
confidence: 99%